Relationship of Sherlock Holmes and John Watson in Mark Gatiss’s Sherlock Television Series - Yoane M. Trianida; Meilinda Meilinda (Institute of Research and Community Outreach - Petra Christian University, 2015)
This thesis aims to reveal the interdependency between Sherlock Holmes and John Watson in Sherlock television series. Their interdependency can be in a form of social needs or emotional needs. To fulfill their needs, both of them need an attachment toward each other. Thus, their attachment develops into an interdependency relationship. In fulfilling their needs, both of them doing the exchange process between cost and reward form their relationship. Also, there are some reasons which made both of them develop a very close relationship. In conclusion, Sherlock and John have their own outcomes or rewards which can be achieved only in their relationship. Also, Sherlock and John, in order to fulfill their emotional or social needs they have to bear the consequence